Testosterone is associated with cooperation during intergroup competition by enhancing parochial altruism - Reimers, Luise; Diekhof, Esther K. (Frontiers in Neuroscience, 2015)
The steroid hormone testosterone is widely associated with negative behavioral effects, such as aggression or dominance. However, recent studies applying economic exchange tasks revealed conflicting results. While some point to a prosocial effect of testosterone by increasing altruistic behavior, others report that testosterone promotes antisocial tendencies. Taking into account additional factors such as parochial altruism (i.e., ingroup favoritism and outgroup hostility) might help to explain this contradiction. First evidence for a link between testosterone and parochial altruism comes from recently reported data of male soccer fans playing the ultimatum game. In this study high levels of endogenous testosterone predicted increased altruistic punishment during outgroup interactions and at the same time heightened ingroup generosity. Here, we report findings of another experimental task, the prisoner’s dilemma, applied in the same context to examine the role of testosterone on parochial tendencies in terms of cooperation. In this task, fifty male soccer fans were asked to decide whether or not they wanted to cooperate with partners marked as either fans of the subject’s own favorite team (ingroup) or fans of other teams (outgroups). Our results show that high testosterone levels were associated with increased ingroup cooperation during intergroup competition. In addition, subjects displaying a high degree of parochialism during intergroup competition had significantly higher levels of testosterone than subjects who did not differentiate much between the different groups. In sum, the present data demonstrate that the behavioral effects of testosterone are not limited to aggressive and selfish tendencies but may imply prosocial aspects depending on the context. By this means, our results support the previously reported findings on testosterone-dependent intergroup bias and indicate that this social hormone might be an important factor driving parochial altruism.